PERAN KERJASAMA PERTUKARAN DALAM PENCIPTAAN KEUNGGULAN BERSAING PERUSAHAAN; SEBUAH KERANGKA KERJA KONSEPTUAL - Setyo Hartono, R. Djoko (STIE Totalwin Semarang, 2013)
Facing uncertain environtment, firms have strived to achieve greater exchange collaboration to leverage the resources and knowledge of customer. The objective of the study is to uncover the nature of exchange collaboration and explore its impact on firm competitive advantage. The results indicate that exchange collaboration has a significant impact on firm competitive advantage.Â